Optimization of Marketing on MSMES “Susu Dan Yogurt Marinos” at District Musuk, Boyolali Regency (Indonesian Journal of Devotion and Empowerment, 2022)
This program aims to pioneer and foster MSMEs Milk Marinos in overcoming the marketing of milk produced by farmers in Dukuh Gatakrejo RT 04/02, Sukorejo Village, Kec. Musuk, Boyolali Regency. Considering the number of milk that is not sold, then as an alternative, make milk pasteurized with various flavors that have a longer shelf life. This pasteurization will increase its selling value and shelf life by producing it as milk and expanding its marketing. The program also aims to accelerate the diffusion of SME technology and management. As well as develop a link and match process between universities, SMEs, governments, and the community. This program begins with designing and manufacturing production equipment, mainly a moisturizer with a capacity of 50 liters equipped with UV light so that the products produced are sterile. The existence of such tools needs to be given technical guidance to employees involved in the production process. In addition, it is also given counseling about clean and halal production. In order to ensure the quality of production, it is sought to obtain an MD certificate from the Food and Drug Control Center of Central Java Province. The requirements for the certificate to be obtained, it is necessary to build and structure the production room, its equipment, and the necessary laboratories. The production room must always be sterile, with equipment ready for production purposes and packing until it is ready to be marketed. This program is expected to provide solutions to overcome the problem of selling farmers' livestock milk and increase its selling value, which means it will increase the income of existing dairy farmers. Kegiatan Pengabdian Kepada Masyarakat Program ini bertujuan untuk merintis dan membina UMKM Susu Marinos dalam mengatasi pemasaran susu hasil peternak di Dukuh Gatakrejo RT 04/02, Desa Sukorejo, Kec. Musuk, Kabupaten Boyolali. Mengingat banyaknya susu yang tidak terjual, maka sebagai alternatif dengan dibuat susu pasturisasi dengan berbagai rasa yang mempunyai daya simpan lebih lama. Dengan diproduksinya sebagai susu pasturisasi ini akan meningkatkan nilai jual, daya simpan dan memperluas pemasarannya. Program juga bertujuan untuk mempercepat difusi teknologi dan manajemen UKM, serta mengembangkan proses link and match antara Perguruan Tinggi, UKM, Pemerintah dan masyarakat. Program ini diawali dengan perancangan dan pabrikasi alat produksi, utamanya adalah pasturizer dengan kapasitas 50 liter yang dilengkapi sinar UV agar produk yang dihasilkan steril. Adanya alat tersebut perlu diberikan bimbingan teknis kepada pegawai yang terlibat pada proses produksi. Disamping itu juga diberikan penyuluhan tentang produksi bersih dan halal. Guna menjamin kualitas produksinya maka diupayakan untuk mendapatkan sertifikat MD dari Balai Pengawasan Obat dan Makanan Provinsi Jawa Tengah. Untuk memenuhi persyaratan agar diperoleh sertifikat MD tersebut diperlukan pembinaan dan penataan ruang produksi dan perlengkapannya serta laboratorium yang diperlukan. Ruang produksi harus selalu steril dengan perlengkapan yang memadahi untuk keperluan produksi, pengepakan hingga siap untuk dipasarkan. Adanya program ini diharapkan dapat memberikan solusi dalam mengatasi masalah penjualan susu hasil ternak petani dan akan meningkatkan nilai jualnya yang berarti akan meningkatkan pendapatan peternak sapi perah yang ada.